Ocular manifestations in COVID-19 Patients at Dr. Wahidin Sudiro Husodo General Hospital Mojokerto during January – June 2021 - Rini Kusumawar Dhany; Gusti Ratu Azzahra (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2023)
Coronavirus Disease (COVID-19) is a respiratory infection caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). SARS-CoV-2 can be found in ocular organs through direct inoculation, migration via the nasolacrimal duct, or hematogenous. This study aims to determine the clinical manifestations of eye disease in COVID-19 patients at Dr. Wahidin Sudiro Husodo Mojokerto General Hospital from January-June 2021. A cross-sectional retrospective observational study by collecting secondary data on patient medical records. The research sample was all outpatients and inpatients with a positive PCR test for COVID-19 who were consulted by an ophthalmologist at Dr. Wahidin Sudiro Husodo General Hospital Mojokerto in January-June 2021. A total of 861 cases of patients with positive PCR tests for COVID-19, a total of 67 patients were consulted to eye specialists with a median age of 42.6 years. Among 67 patients, 59 (88%) showed symptoms of conjunctival injection, 8 patients (12%) ciliary infusion with 7 patients diagnosed with keratitis, and 1 patient with ulcer redness. In conclusion, the main eye manifestation most commonly found in COVID-19 patients is conjunctivitis which is characterized by conjunctival hyperemia.